(untitled) (Revista Científica Ciencias Naturales y Ambientales, 2025)
Currently, one of the most important challenges in aquaculture is production costs, with balanced feed being the most determining factor in operational expenses. In Ecuador, the cultivation of chame (Dormitator latifrons) constitutes a striking aquaculture option to diversify local production due to its low cultivation cost and important ecological role. In this study, the effect of biofloc systems on a culture of chame juveniles was evaluated by determining physicochemical and zootechnical parameters such as weight gain (GP), average length (cm), specific growth rate (SGR) and survival rate. The results showed that the biofloc system, used as a supplementary food source, significantly improved the growth of chame juveniles (GP: 4.10±0.10a) compared to a traditional culture with daily water exchanges. Key words: Biofloc, chame, production, weight gain.